2003
DOI: 10.1046/j.1468-1293.2003.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV/HBV and HIV/HCV coinfection, and outcomes following highly active antiretroviral therapy

Abstract: ObjectivesTo assess the prevalence and risk factors for HBV and HCV coinfection in the Australia HIV Observational Database (AHOD), and examine outcomes of HIV disease following initiation of highly active antiretroviral therapy (HAART).MethodsAnalyses were based on 2086 participants recruited to AHOD by September 2002. Of these, 1605 (77%) had been tested for HBV surface antigen, 1704 (82%) for anti‐HCV antibody and 1453 (70%) for both. Demographic and clinical predictors of HBV and HCV coinfection were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
104
3
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 21 publications
20
104
3
5
Order By: Relevance
“…Studies previously have proposed that dual positivity of HIV/HBV or HIV/HCV and triple positivity HIV/HBV/HCV have dampened immune reaction to HAART likened with those with only HIV [40][41][42] . While others studies have reported some degrees of immune reinstatement in individuals with HIV/HBV or HIV/HCV dual-infection [42][43][44][45][46][47][48] . Management of either hepatitis virus is multifaceted because of pharmacokinetic interfaces with constituents of HAART regimens.…”
mentioning
confidence: 94%
“…Studies previously have proposed that dual positivity of HIV/HBV or HIV/HCV and triple positivity HIV/HBV/HCV have dampened immune reaction to HAART likened with those with only HIV [40][41][42] . While others studies have reported some degrees of immune reinstatement in individuals with HIV/HBV or HIV/HCV dual-infection [42][43][44][45][46][47][48] . Management of either hepatitis virus is multifaceted because of pharmacokinetic interfaces with constituents of HAART regimens.…”
mentioning
confidence: 94%
“…13,[16][17][18][19] Only a limited number of studies have examined association between other comorbidities in relation to their effect on hepatitis vaccine efficacy among patients infected with HIV. 20 In reviewing the scientific literature related to drug and alcohol use in relation to CD4 counts, we reviewed 1 study reporting that persons using drugs or alcohol had statistically significant decreases in CD4 counts; however, no studies evaluated the effects of other substances on immunity development. 21 This analysis provides information for the medical community regarding HAV/HBV vaccination among patients living with HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…However, the estimated prevalence of these coinfections in the Spanish HIV population (37% and 20-50% respectively) is greater than in the Australian (6% and 13% respectively). [17][18][19] The primary limitation of BICOMBO and STEAL, and therefore this combined analysis, was the inclusion of participants who were not naïve to TDF and ABC. However stratification by baseline NRTI showed no significant interaction between baseline exposure to ABC/ TDF and randomised treatment for any outcome.…”
Section: Discussionmentioning
confidence: 99%